Acquired haemophilia A presenting at a District General Hospital. (17th February 2015) - Freeman, Amy
Abstract : We report a case of a 64-year-old man presented to A&E with a 2-week to 4-month history of right hip pain, right leg weakness and fasciculations, extensive bruising and a vesicular skin rash. He had a CT of the chest/abdomen/pelvis, which revealed multiple extensive haematomas including an iliopsoas haematoma causing a lumbar plexopathy and resulting in the right hip and leg symptoms. He had clotting studies showing a prolonged activated partial thromboplastin time. Haematology review together with mixing studies suggested a diagnosis of acquired haemophilia A. He was treated at the local tertiary centre with activated prothrombin complex concentrate and steroids and made a full recovery.